Medium Resolution Lunar Topography: An Updated View of the Lunar Surface from Stereophotogrammetrically Derived DTMs - J. R. Laura; O. Alexandrov; L. Adoram-Kershner; K. Bauck; B. H. Wheeler; T. M. Hare (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Digital Terrain Models (DTMs) are essential for lunar exploration, supporting critical applications such as landing site selection, mission planning, and in-situ resource utilization. This study presents a comprehensive reprocessing of the Kaguya Terrain Camera (TC) dataset using the NASA Ames Stereo Pipeline to generate over 130,000 medium-resolution DTMs with nearly global lunar coverage to ±70°. We observed significant bowing in the DTMs derived using the publicly available interior orientation and have used a novel technique, in the planetary sciences, to re-estimate the boresight and eight-parameter distortion coefficients. We present a jitter correction methodology to correct for vertical alignment errors in the DTMs. DTMs are aligned to the Lunar Orbiter Laser Altimeter (LOLA) point cloud and absolute errors are mean centered to zero with a mean standard deviation of 24 meters. We achieved horizontal accuracies inside the orthoimage resolution (mean of 30 meters per pixel) and 2—4 meters vertically. The methods and insights gained from this large-scale processing effort establish a framework for automating DTM derivation with other planetary data sets.